Carbon molecular sieve membranes comprising graphene oxides and porous carbon for CO₂/N₂ separation - Chuah, Chong Yang (2021)
To improve the CO₂/N₂ separation performance, mixed-matrix carbon molecular sieve membranes (mixed-matrix CMSMs) were fabricated and tested. Two carbon-based fillers, graphene oxide (GO) and activated carbon (YP-50F), were separately incorporated into two polymer precursors (Matrimid® 5218 and ODPA-TMPDA), and the resulting CMSMs demonstrated improved CO₂ permeability. The improvement afforded by YP-50F was more substantial due to its higher accessible surface area. Based on the gas permeation data and the Robeson plot for CO₂/N₂ separation, the performances of the CMSMs containing 15 wt % YP-50F and 15 wt % GO in the mixed polymer matrix surpassed the 2008 Robeson upper bound of polymeric membranes. Hence, this study demonstrates the feasibility of such membranes in improving the CO₂/N₂ separation performance through the appropriate choice of carbon-based filler materials in polymer matrices.